Effect of Hydrochloric Acid on Formation of Nanocrystalline Bismuth Phosphate Synthesized via Hot Injection Method - Lee, S.L.; Yong, S.W.; Hartini, K.O. (Asian Journal of Chemistry, 2013)
An attempt was made to synthesize nanocrystalline bismuth phosphate via hot injection method. The effect of hydrochloric acid concentration used during the synthesis process was investigated. The acid acted as oxidizing agent in producing PH3, the phosphorus source which reacted with bismuth acetate in 1-octadecene solvent. The XRD patterns showed the materials crystallined in cubic phase when 2 M or 4 M HCl were used. Meanwhile, a minor impurity phase of BiOCl was detected when higher concentration of 6 M or 8 M HCl was applied. It has been demonstrated that the particle size of these single phase materials ranged 5-7 nm. Interestingly, different particle shapes were observed in the bismuth phosphate materials that were prepared using varied concentration of HCl during synthesis process via hot injection method.